Clinical evaluation of fibre-optic sigmoidoscopy employing the Olympus CF-SB colonoscope. Issue 9 (September 1971) - Salmon, P. R.; Branch, R. A.; Collins, C.; Espiner, H.; Read, A. E.
Abstract : Fifty-one patients with large bowel disease were examined with the Olympus CF-SB fibreoptic colonoscope. With adequate bowel preparation and employing inhalational analgesia administered by a self-demand valve the whole sigmoid colon could be examined in the majority of patients within 30 minutes. In 23% of cases (12/51) the diagnosis was either made or confirmed by this procedure alone. Fibreoptic sigmoidoscopy is especially helpful in patients with either equivocal or failed barium enemas and is indicated in patients with unexplained rectal bleeding, extending the search for polyps and cancer, and studying patients with inflammatory bowel disease. About one quarter of biopsies taken from a flat mucosal surface with the Olympus flexible biopsy forceps may be insufficient for detailed histology due to their small size. For this reason multiple biopsies may be taken. Adequate biopsies were always obtained from projecting lesions and could be very accurately sited. Colour photography employing automatic exposure control is used to supplement the information obtained. It is concluded that fibreoptic sigmoidoscopy is a valuable additional investigation in selected patients with suspected disease of the large bowel and to date has been without complications.